Parliamentary Opposition Under Hybrid Regimes: Evidence from Egypt. Issue 4 (4th July 2016) - Loidolt, Bryce; Mecham, Quinn
Abstract : Why do opposition political parties choose to run for parliament in semiauthoritarian systems? Existing literature emphasizes the benefits that these parties derive from campaigning and running for elections, while paying little attention to the politics that occurs within legislative institutions under these regimes. Supplementing election‐centric theories, we argue that opposition actors in semiauthoritarian systems also benefit directly from serving in weak parliaments and that this helps explain their participation in biased elections. We demonstrate this by examining the Muslim Brotherhood's legislative performance in Mubarak's Egypt, highlighting the mechanisms through which it used its minority presence in parliament to its advantage.